2018
DOI: 10.1186/s13717-018-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and carbon stock inventory of high-altitude dry temperate land use systems in North Western Himalaya

Abstract: Introduction: Carbon stock estimation in different land use systems is necessary for curbing global climatic crisis. In the present study, high-altitude dry temperate land use systems (LUS) at three altitudinal ranges "A 1, 1900-2170 m. a.s.l., A 2, 2170-2440 m.a.s.l., and A 3, 2440-2710 m.a.s.l." were selected based on lapse rates in Kinnur district of Himachal Pradesh, India. The study was aimed at estimating the difference in biomass and carbon stocks in different land use systems and recommendation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 25 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Since trees during their initial stages of growth i.e., when their DBH is lower will thus sequester less carbon but gradually as it increase in DBH would accumulate more carbon. Moreover, it has been observed younger trees grow much faster than older trees as also studied by Chisanga et al (2018). This study was in conformity with the findings of Huston and Marland (2003), who showed that carbon sequestration depends not only on rates of productivity, but also on the size of tree.…”
Section: Resultssupporting
confidence: 91%
“…Since trees during their initial stages of growth i.e., when their DBH is lower will thus sequester less carbon but gradually as it increase in DBH would accumulate more carbon. Moreover, it has been observed younger trees grow much faster than older trees as also studied by Chisanga et al (2018). This study was in conformity with the findings of Huston and Marland (2003), who showed that carbon sequestration depends not only on rates of productivity, but also on the size of tree.…”
Section: Resultssupporting
confidence: 91%
“…Different natural and anthropogenic activities in the forest floor promote SOC accumulation by exposing it to higher levels of microbial activity [32]. Counting all these points, elevational gradients could become the most powerful "natural triggers" for monitoring the ecological and evolutionary responses of biota to environmental changes [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Our study clearly demonstrated wide variations in physical and chemical properties of soil across various land use systems down the soil profile. The literature also suggests that the physico‐chemical properties of soil vary depending upon existing land use and its management regimes (Chisanga et al, 2018; Juhos et al, 2019; Silva‐Olaya et al, 2022). The observed range of BD, porosity and pH in this study corroborates well with the previous studies on various land use systems ranging from agricultural, horticultural, pasture, fallow/wasteland to rangeland of the NWH region (Bargali et al, 2019; Bargali & Bargali, 2020; Debnath, Narayan, et al, 2020; Loria et al, 2016; Meena et al, 2018).…”
Section: Discussionmentioning
confidence: 99%